Addition of various unsaturated alcohols to sulfonylisocyanate derivatives: Synthesis of new unsaturated N-sulfonyl carbamates. (3rd May 2016) - Radhouani, Ahlem; Beji, Mohamed
GRAPHICAL ABSTRACT: Abstract: The synthesis of new unsaturated N-sulfonylcarbamates by the addition of unsaturated alcohols to aroxy(alkoxy)sulfonylisocyanates is reported. The reaction is carried out at room temperature in the presence or absence of solvent, depending on the nature of the starting alcohol. The products were obtained in good yields and characterized with IR, 1 H, and 13 C NMR and HRMS analyses.